1992
DOI: 10.1046/j.1468-2982.1992.1203178.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Facial Pain as The First Symptom of Lung Cancer: Are There Diagnostic Clues?

Abstract: We describe three patients with unilateral facial pain due to non-metastatic lung cancer and review 11 published cases. Pain, most frequently located on the right side and around the ear, as well as digital clubbing can be clues to an early diagnosis. Compression of the vagus nerve by the tumour or by mediastinal adenopathy is most likely responsible for the facial pain and could play a role in pulmonary osteoarthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Rarely, unilateral facial pain can herald the diagnosis of intrathoracic, nonmetastatic lung cancer. In previous reports of such an association, the underlying cancer was most often discovered on routine chest radiograms 1,3‐13 . We report 2 cases of facial pain associated with lung cancer in which an initial chest film failed to detect underlying malignancy.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Rarely, unilateral facial pain can herald the diagnosis of intrathoracic, nonmetastatic lung cancer. In previous reports of such an association, the underlying cancer was most often discovered on routine chest radiograms 1,3‐13 . We report 2 cases of facial pain associated with lung cancer in which an initial chest film failed to detect underlying malignancy.…”
mentioning
confidence: 84%
“…The combined medical literature to date has documented 31 cases from which a common clinical pattern has emerged. All of these patients presented with atypical unilateral facial pain and were ultimately diagnosed with ipsilateral lung carcinoma 1,3‐13 . Key clinical features are summarized in the Table 1.…”
Section: Commentsmentioning
confidence: 99%
“…Orofacial pain referred from non-metastatic cancer is very rare but it has been reported that lung cancer and mediastinal malignant disease secondary to lung cancer can refer orofacial pain in the ipsilateral side (37,38). This referred pain could be provoked by compression of the vagus nerve by the lung (or any other organ or structure along the nerve), causing a convergence of somatic and visceral afferent inputs to the trigeminal nucleus caudalis, causing pain symptomatology in these regions (39).…”
Section: Orofacial Pain As a Symptom Of Cancermentioning
confidence: 99%
“…This referred pain could be provoked by compression of the vagus nerve by the lung (or any other organ or structure along the nerve), causing a convergence of somatic and visceral afferent inputs to the trigeminal nucleus caudalis, causing pain symptomatology in these regions (39). The pain has been described as intractable, unexplained, debilitating, severe, aching and paroxysmal, and with a poor response to therapy (37,38,40,41). Furthermore, neuralgic symptoms such as trigeminal neuralgia have been reported as the only symptom of pancreatic cancer (42).…”
Section: Orofacial Pain As a Symptom Of Cancermentioning
confidence: 99%
“…(Jones & Lawson, 1987;Bindoff & Heseltine,1988;Nestor, 1991;Broux 1991;Bongers et al, 1992;Schoenen et al, 1992;Nestor & Ngo, 1994;Capobianco, 1995;Shakespeare & Stevens, 1996;Goldberg, 1997;Abraham et al, 2003;Sarlani et al, 2003;Eross et al, 2003;Demez et al, 2004;Palmieri, 2006). However, the central connections responsible for referred pain in such clinical cases have not been thoroughly reviewed.…”
Section: Introductionmentioning
confidence: 99%